Visual Sensory Experiences From the Viewpoint of Autistic Adults - Parmar, Ketan R.; Porter, Catherine S.; Dickinson, Christine M.; Pelham, James; Baimbridge, Peter; Gowen, Emma (Frontiers in Psychology, 2021)
Although previous research has investigated altered sensory reactivity in autistic individuals, there has been no specific focus on visual sensory experiences, particularly in adults. Using qualitative methods, this study aimed to characterize autistic visual sensory symptoms, contextualize their impact and document any associated coping strategies. A total of 18 autistic adults took part in four focus groups which involved questions around visual experiences, the impact of these on daily life, and strategies for their reduction. Transcripts of each session were thematically analyzed allocating six key themes. Participants described a range of visual hypersensitivities, including to light, motion, patterns and particular colors, which contributed to distraction and were frequently part of a wider multisensory issue. Such experiences had significant negative impacts on personal wellbeing and daily life with participants describing fatigue, stress and hindrances on day-to-day activities (e.g., travel and social activities). However, the degree of understanding that participants had about their visual experiences influenced their emotional response, with greater understanding reducing concern. Participants employed a variety of coping strategies to overcome visual sensory experiences but with varied success. Discussions also highlighted that there may be a poor public understanding of sensory issues in autism affecting how well autistic individuals are able manage their sensory symptoms. In summary, autistic adults expressed significant concern about their visual experiences and there is a need to improve understanding of visual experiences on a personal and public level as well as for developing potential support.